A Legal Appraisal of the Causes of the Cameroon Anglophone Crisis - Orzende Hans Iyal Ph.D.; Nkongho Elizabeth; Enow Godwill Baiye Ph.D. (Studies in Social Science & Humanities, 2024)
The Cameroon Anglophone Crisis, which erupted in 2016, stems from longstanding grievances among the Anglophone population regarding marginalization, governance issues, and cultural rights within a predominantly Francophone nation. This legal appraisal examines the historical context, highlighting the post-colonial legacy that has shaped Anglophone identity and political aspirations. It analyzes the key main Causes of the anglophone crisis bringing out facts such the constitutional problem, socio-political causes and the role of the diaspora and the media. The study adopts a qualitative research methodology which makes use of the doctrinal method as one of the main methods which deals with content analysis of primary and secondary data. Unstructured interviews and observation were also used as part of the methods of obtaining data. The ensuing results reveals that the main cause of the crisis is one of ideology which was birthed as far as the period of reunification which has remain unaddressed till date. Hence, it laid a foundation for the researcher to recommend a sincere and all-inclusive dialogue amongst the concerned parties amongst others.